Study and characterization of modified silicon surfaces with organic molecules - Valpuesta-Fernández, María; Sánchez-Molina, María; Lucena-Serrano, Ana; Contreras-Cáceres, Rafael; López-Romero, Juan Manuel; Díaz-Morilla, Amelia (My University, 2016)
Nanostructured thin films and subsequent biofunctionalization of silicon substrates are essential for the development of biosensors devices. The formation of organic monolayers on silicon substrates via Si-C bound allows specific interactions with biomolecules and presents several advantages like greater detection sensitivity and stability against hydrolytic cleavage.1 In this sense, to control the orientation and spacing between grafted functional moieties on the surface, tripodal oligo (p-phenylene)s have become ideal anisotropic adsorbates due to their shape-persistent and selfstanding characteristics.2 On the other hand, biomolecules such as tehtahydro[3]benzazepines are well-known to contain in their structure a phenetylamine skeleton, which is also present in dopaminergic receptors and drugs, therefore these molecules have a remarkable interest in medicinal chemistry. Here we report the synthesis and characterization of several tetrahydro[3]benzazepines and tripod-shaped oligo(p-phenylene)s which were suitably functionalized for its subsequent adsorption on silicon surfaces by hydrosilylation and/or CuAAc click reaction. X-ray photoemission spectroscopy (XPS) and atomic force microscopy (AFM) analysis were also carried out to reveal the presence of the grafted molecules on the different Si surfaces.
Keywords: Biomoléculas; Benzazepines; Tripod-shaped molecules; Silicon surfaces; Nanostructuration; Functionalization